2002
DOI: 10.1080/00039420214191
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Responses to Different Dietary Cereal Types and Xylanase Supplementation in the Intestine of Broiler Chicken

Abstract: Several studies were carried out to investigate the influence of dietary cereals differing in soluble non starch polysaccharides (NSP) content and a xylanase preparation on selected bacterial parameters in the small intestine of broiler chicken. Compared to a maize diet colony forming units (CFU) of mucosa associated bacteria were higher in a wheat/rye diet, most notably for enterobacteria and enterococci. Xylanase supplementation to the wheat/rye diet generally led to lower CFU, especially in the first week o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
2
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(88 citation statements)
references
References 31 publications
4
77
2
5
Order By: Relevance
“…Piel et al (2005) showed that ingestion of highly viscous carboxymethylcellulose increased the number of ileal acidomucin and sulfomucin goblet cells and luminal crude mucin in pigs. This is consistent with the results of Ito et al (2009), who found that viscous fibres up-regulated baseline secretion of small intestinal mucins by increasing the number of goblet cells in proportion to their own viscosities. The explanation responsible for the increase in goblet cells after ingestion of viscous water-soluble fibre was hypothesized to be associated with increased intestinal intraluminal pressure by viscous fibres (Ito et al, 2009).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Piel et al (2005) showed that ingestion of highly viscous carboxymethylcellulose increased the number of ileal acidomucin and sulfomucin goblet cells and luminal crude mucin in pigs. This is consistent with the results of Ito et al (2009), who found that viscous fibres up-regulated baseline secretion of small intestinal mucins by increasing the number of goblet cells in proportion to their own viscosities. The explanation responsible for the increase in goblet cells after ingestion of viscous water-soluble fibre was hypothesized to be associated with increased intestinal intraluminal pressure by viscous fibres (Ito et al, 2009).…”
Section: Discussionsupporting
confidence: 82%
“…Numerous studies have shown that diets with high amounts of wheat and barley increase the intestinal content viscosity caused by water-soluble cell wall or non-starch polysaccharides, thereby resulting in a greater incidence of NE than corn-based diets (Kaldhusdal & Hofshagen, 1992;Kaldhusdal & Skjerve, 1996;Engberg et al, 2004;Jia et al, 2009). The mechanism underlying this effect has been suggested to be that high intestinal viscosity reduces nutrient absorption by the host bird, decreases the rate of feed passage (Choct & Annison, 1992;Almirall & Esteve-Garcia, 1994), and may enhance mucus production (Langhout et al, 1999;Piel et al, 2005;Ito et al, 2009), which could lead to increased numbers of anaerobic bacteria in the intestine, particularly C. perfringens (Hü bener et al, 2002;Kocher, 2003;Engberg et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have been undertaken to determine the influence of dietary changes on the structure of the gut microbial community, by using microbiological culturing techniques, culture-independent molecular techniques and indirect measurement of bacterial metabolic products (Bjerrum et al 2006;Choct et al 1999;Hubener et al 2002;Zhu et al 2002;Yin et al 2010). However, understanding how diet-induced changes in the composition of the gut bacterial community relate to important metabolic changes, and ultimately to broiler health and performance, is less clear.…”
Section: Introductionmentioning
confidence: 99%
“…Ainsi, soucieuses de connaitre le mode d'action des antibiotiques, ces équipes recherchèrent les modulations de la flore face à de nombreux antibiotiques (Zhou et al, 2007 ;. Puis, dans la continuité, des tests furent entrepris sur de nombreux probiotiques (Gerard et al, 2008 ;Vahjen et al, 2002 ;Lan 33 et al, 2004) et prébiotiques (Hubener et al, 2002) (Van Deun et al, 2008), Clostridium perfringens (Skanseng et al, 2006) ou Escherichia coli (Mellata et al, 2003). animale, la prophylaxie ou la désinfection à outrance ont été favorable à l'apparition de souches multirésistantes et ce, par le simple jeu de la sélection naturelle.…”
Section: A 2 Les Microflores Digestivesunclassified